A trickle-down effect of subordinates' felt trust. Issue 4 (4th June 2019) - Chiu, Han-Cheng; Chiang, Pin-Hua
Abstract : Purpose: The purpose of this paper is to examine the relationships between managers' and supervisors' trust in subordinates and team cooperation and to suggest that the downward flow of trust affects team employees. Design/methodology/approach: Data were collected from supervisor-employee dyads from a multisource field study. Findings: Feeling trusted by managers has an indirect effect on team cooperation through feeling trusted by supervisors. In addition, there was a strong positive relation between feeling trusted by supervisors and team cooperation when team size was smaller, but a weak positive relation when team size was larger. Practical implications: In order for subordinates to feel trusted, management leaders must implement actions that include: delegation and empowerment, participative decision-making and listening with respect and full attention. It is also suggested that the team size should not be too large. Originality/value: We integrate theories of social exchange, social information processing, social learning and attraction-selection-attrition to test a trickle-down model of how trust in subordinates cascades down through management levels and ultimately affects team cooperation.